Proactive experiences of vibrotactile stimuli enhance learners’ task-specific confidence in cooking skills - Inoue, Sana; Komazaki, Kakagu; Wada, Yuji; Watanabe, Junji (Frontiers in Virtual Reality, 2026)
In skill acquisition, learners’ motivation plays an important role. Based on embodied cognition and haptic learning, we hypothesized that vibro-acoustic stimuli could serve as valuable feedback to enhance motivation. In this study, three experiments explored whether such stimuli strengthen learners’ task-specific confidence in their cooking abilities. Experiment 1 examined the discriminability of vibro-acoustic stimuli as feedback. Sounds and vibrations were recorded when a professional chef and an amateur cut two types of food, and were presented via a haptic device to participants, who evaluated the sensations. Participants successfully distinguished between the two performers solely through the vibro-acoustic stimuli. Experiments 2 and 3 investigated how vibro-acoustic stimuli corresponding to food cutting affect task-specific confidence. Participants who actively experienced the stimuli while watching a professional chef’s video showed greater confidence than those who only felt the stimuli passively. These findings point to the potential applicability of vibro-acoustic stimuli in facilitating certain aspects of cooking skill acquisition, although the current work is an exploratory step toward integrating haptic cues into cooking education rather than a demonstration of performance improvement.